Gambaran Perilaku Tidak Aman Pekerja Pada Ketinggian Dan Determinannya - Riastuti Kusuma Wardani; Diva Muhammad Alviansyah; Iting Shofwati; Minsarnawati (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2025)
The main cause of work accidents due to falls from heights was unsafe behavior. In the Jakarta LRT Project, there were still unsafe behaviors performed by workers at heights such as not use complete PPE, not hooking FBH (Full Body Harness) to lifelines or scaffolding, not follow safety procedures, and smoke while working at heights. This research aimed to describe the unsafe behavior and determinants in the workers at heights in the Jakarta LRT Project Phase 1B Velodrome-Manggarai Zone 2 in 2025. This research used quantitative methods with a cross-sectional design and was conducted from January to May 2025. The sample was workers at heights using random sampling techniques and obtained 73 respondents. Data analysis used descriptive analysis. The research results showed that 72 workers (98.6%) behaved unsafely with the highest percentage of unsafe behavior being 71% of workers had never reported work conditions and hazard and risk findings to supervisors. The description of determinants of unsafe behavior showed that most workers had poor knowledge, did not comply with safety procedures, had never received occupational health and safety training, had poor supervision, rarely received rewards, and rarely received punishment. HSE personnel need to educate workers about the dangers and safe working practices when working at heights and increase supervision to ensure compliance with safety procedures. Management needs to re-conduct training on working at heights and safe use of scaffolding for workers and increase the number of award recipients and strengthen the punishment for workers. Keywords: Unsafe Behavior, Construction, Workers at Heights